Goat performance on pure Andropogon gayanus pastures or associated with legumes - Moura, Raniel Lustosa de; Oliveira, Maria Elizabete de; Carvalho, Wanderson Fiares de; Rodrigues, Marconio Martins; Santos, Maurilio Souza dos; Edvan, Ricardo Loiola; Abdalla, Adibe Luiz [UNESP]; Moreira, Marcelo Zacharias [UNESP]; Silva, Edson Mendes da (Springer, 2021)
The objective of this study was to evaluate the grazing of goats in a grass monoculture system and in intercropping systems of grass + legumes. A randomized block design was adopted, with the treatments arranged in a split-plots scheme. The plots consisted of three cropping systems: monoculture-Andropogon gayanus cv. Planaltina; mixture I-A. gayanus cv. Planaltina +Stylosanthes cv. Campo Grande; and mixture II-A. gayanus cv. Planaltina +Calopogonium mucunoides. The subplots consisted of two grazing cycles. The highest (P=0.04) total forage mass (TFM) was recorded in the mixture I (A. gayanus cv. Planaltina+Stylosanthes. cv. Campo Grande), which was 2.6 +/- 0.1 tons DM/ha. The crude protein (CP) was lower in the monoculture which also showed the highest content of neutral detergent fiber (NDF). The grazing time in the monoculture was the longest (8.23 +/- 1.14 h). The goats used a longer time for rumination (P<0.01) in the mixture I. The lowest (P<0.01) bite rate was found in mixture II in comparison to the other cropping systems. The bite rate was higher (P<0.01) in grazing cycle II than in all the other cropping systems. In mixture I, the Stylosanthes cv. Campo Grande, and in mixture II, the C. mucunoides presented the lowest (P<0.01) delta C-13 value in the forage. The highest forage intake occurred in the mixture systems (P<0.01) in comparison to the monoculture. The mixture pastures presented better results for forage mass, nutritive value, and intake in comparison to the monoculture.
Keywords: Behavior; Calopogonium mucunoides; Digestibility; Intake; Isotopes; Stylosanthes cv; Campo Grande